Arterial abnormalities identified in kidneys transplanted into children during the COVID‐19 pandemic. Issue 5 (18th February 2021) - Berteloot, Laureline; Berthaud, Romain; Temmam, Sarah; Lozach, Cécile; Zanelli, Elisa; Blanc, Thomas; Heloury, Yves; Capito, Carmen; Chardot, Christophe; Sarnacki, Sabine; Garcelon, Nicolas; Lacaille, Florence; et al.
Abstract : Graft artery stenosis can have a significant short‐ and long‐term negative impact on renal graft function. From the beginning of the COVID‐19 pandemic, we noticed an unusual number of graft arterial anomalies following kidney transplant (KTx) in children. Nine children received a KTx at our center between February and July 2020, eight boys and one girl, of median age of 10 years. Seven presented Doppler features suggesting arterial stenosis, with an unusual extensive pattern. For comparison, over the previous 5‐year period, persistent spectral Doppler arterial anomalies (focal anastomotic stenoses) following KTx were seen in 5% of children at our center. We retrospectively evidenced severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in five of seven children with arterial stenosis. The remaining two patients had received a graft from a deceased adolescent donor with a positive serology at D0. These data led us to suspect immune postviral graft vasculitis, triggered by SARS‐CoV‐2. Because the diagnosis of COVID‐19 is challenging in children, we recommend pretransplant monitoring of graft recipients and their parents by monthly RT‐PCR and serology. We suggest balancing the risk of postviral graft vasculitis against the risk of prolonged dialysis when considering transplantation in a child during the pandemic. Abstract : Among children undergoing kidney transplantation during the COVID‐19 pandemic, the authors find a high incidence of arterial abnormalities attributed to SARS‐CoV‐2–triggered immune vasculitis that leads to recommendation for pretransplant virological and serological monitoring and posttransplant Doppler follow‐up.